Enabling - Beyond Empowering - Williams, Michael (London : Thorogood Herndon : Stylus Publishing, LLC [Distributor], 1998)
Annotation Enabling, like empowering, is about providing people with the authority and means to do what needs to be done, but in a way that substantially reduces or removes the dangers.This Special Briefing clearly explains how this can be achieved by applying a range of practical management techniques in the right place, and at the right time.
Trade